Hit Probability Bayesian Network for Sea Battles - David Artanto; Trika Pitana; Udisubakti Ciptomulyono (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Many factors affect the hit probability in a shooting between surface combatants, which involve the environment where the warfare takes place, the weapons and ammunition used, the shooting personnel and so on. Due to technological developments, these influencing factors can be improved for the better results. These influencing factors are interrelated with each other, and can even reduce each other. Bayesian Network is a method applied for probability analysis that considers the relationship of these influencing factors and is arranged in a Directed Acyclic Graph (DAG). Bayesian network structure is composed of initial information (prior probability) and the relationship between conditional probabilities at each node that have been determined based on expert knowledge or certain analysis. Such conditional probability is only valid for data analysis at the time of collection. In this study, a Bayesian network model for naval warfare, surface ships are involved was developed. The model is based on the results of a literature study and validation based on experienced professionals. The relationship between nodes shows five main influencing factors are fire control system, ammunition, personnel, movement of the target being shot and environmental factors dominated by the marine environment.